New reports of Basidiomycota from Jalisco, Mexico - Rodríguez, Olivia; Herrera-Fonseca, María de Jesús; Galván-Corona, Adrián (Instituto de Ecología, A.C., 2013)
Twenty three new records are reported for the Jalisco mycobiota, mainly pertaining to Agaricales, Hymenochaetales and Russulales. Albatrellus caeruleoporus, Amanita jacksonii, Hydnellum ferrugineum, Hymenochaete damicornis, Pluteus salicinus, Ramaria araiospora var. araiospora and Suillus tomentosus var. discolor are described, and information is provided on their economic importance and ecologic distribution.